Determination of the Fractal Character of the Romanian Capital Market by Using Hurst Exponent - Metescu, Ana-Maria (Acta Universitatis Danubius. Œconomica, 2022)
Failure of classical statistical methods to model the behavior of stock market prices determined, in a domino effect, the failure of the classical paradigm of regarding markets as efficient systems. Alternative to this simple interpretation, markets should be regarded as far from equilibrum dynamical systems, complex evolving structures that encompass millions of participants, holding into their memory events that happened long time ago. This more realistic approach was developed by Fractal Market Hypothesis, as an alternative to Efficient Market Hypothesis. R/S Analysis is a robust tool for testing whether markets follow a Brownian motion or some memory effect is implied. The aim of the paper is to determine the Hurst Exponent, for company ALRO S.A., for the period of time since listing, until 16/07/2021. Results may generate indications about in the nature of the system represented by the prices of ALRO S.A. Conclusion may be that the Romanian capital market, as ALRO is one of the most representative companies listed at Bucharest Stock Exchange, has evolved from a very low stability market to a more stable investment environment.